Firm location, investor recognition, and the liquidity of Chinese publicly listed SMEs - Lim, Kian Ping; Wei Liu; Chia, Yee Ee (Elsevier B.V., 2022)
We assemble data of non-financial stocks on the Shenzhen small and medium-sized enterprise (SME) board over the 2005–2019 sample period to explore the liquidity drivers of listed SMEs. With the complete dominance of retail investors, two competing hypotheses are derived from familiarity. The empirical results reveal the insignificant role of firm location, whereas investor recognition exerts the largest effect on the liquidity of Chinese listed SMEs. This finding implies that having a large pool of potential investors with local bias does not give SMEs headquartered in megacities the home advantage in their quest for higher liquidity. Instead, liquidity improves because considerable shareholders hold stocks that they are familiar with or have knowledge about. The nonlinear relationship, however, highlights the costs of an expanded shareholder base because diffuse ownership exacerbates agency conflicts between the controlling shareholders and small individual investors.